PENGARUH KOMITMEN ORGANISASI DAN PENGETAHUAN DEWAN TENTANG ANGGARAN TERHADAP PERAN DPRD DALAM PENGAWASAN KEUANGAN DAERAH (Studi Pada Kantor Sekretariat DPRD Provinsi Sulawesi Tenggara) - Wawo, Andi Basru; Sarufa, Fitriah (JURNAL AKUNTANSI DAN KEUANGAN, 2016)
Abstract This research aimed of presented to examine the effect of organizational commitment and budgeting knowledge council on the role of regional parliaments in the financial control area. Primary data in this research were obtained from the perception of all members at the Parliament Secretariat of province South east Sulawesi from period of 2014 to 2019. Perceptions of respondents was measured by responses to questionnaires that uses ordinal measurement with a 5-point Likert scale. The analytical tool used to test each hypothesis is multiple regression analysis The results of this research indicate that organizational commitment and budgeting knowledge council partially and simultaneously significant effect on regional Parliament's role in financial control area.The results for the coefficient of determination total organizational commitment and budgeting knowledge council on the role of regional parliaments in the financial control area of R2 = 0.786. This number can be used to see the contribution of the organization's commitment and budgeting knowledge council on role of regional Parliament in the financial control area. The figure has meaning that the contribution of organizational commitment and budgeting knowledge council on role of regional Parliament in the financial control area is 78.6%, while the remaining 21.4% was obtained from the contribution of other factors.Keywords: Organizational Commitment, Budgeting Knowledge Council, Financial Control Area, the role of Regional parliame